Impact of dust on electrical power output of solar PV modules in North-East, Nigeria - Abdulkarim, Hauwa Talatu; Sansom, Christopher L.; Patchigolla, Kumar; Almond, Heather; Karim, Mounia (Niger State College of Education, 2022)
The impact of dust on the solar PV modules deserves more attention. North-eastern Nigeria has high potential of solar irradiance but it is proned to dust accumulation. This paper therefore, investigated the impact of dust on the performance of solar Photovoltaic modules in North-Eastern Nigeria. The investigation entailed field experiment carried out in Maiduguri to assess the performance of the module based on continuous dust deposition for 14 days during dust accumulation period. The results show that more than 50% loss in power output was recorded under 14 days of continuous deposition. The efficiency of the module reduced from 17.1% on the first day to 7.2% on the fourteenth day of the experimentation. The investigation also shows that at high humidity the PV performance drops. Solar irradiance increases the performance. The deployment of solar PV energy supply system is recommended in spite of dust accumulation challenges. To maintain adequate performance of the system, a once a week cleaning is recommended during intense dust accumulation period.
Keywords: Dust; Efficiency; Modules Performance; Photovoltaic; Solar